Evolution of pollination syndromes and corolla symmetry in Balsaminaceae reconstructed using phylogenetic comparative analyses. (22nd October 2020) - Ruchisansakun, Saroj; Mertens, Arne; Janssens, Steven B; Smets, Erik F; van der Niet, Timotheüs
Abstract: Background and Aims: Floral diversity as a result of plant–pollinator interactions can evolve by two distinct processes: shifts between pollination systems or divergent use of the same pollinator. Although both are pollinator driven, the mode, relative importance and interdependence of these different processes are rarely studied simultaneously. Here we apply a phylogenetic approach using the Balsaminaceae (including the species-rich genus Impatiens ) to simultaneously quantify shifts in pollination syndromes (as inferred from the shape and colour of the perianth), as well as divergent use of the same pollinator (inferred from corolla symmetry). Methods: For 282 species we coded pollination syndromes based on associations between floral traits and known pollination systems, and assessed corolla symmetry. The evolution of these traits was reconstructed using parsimony- and model-based approaches, using phylogenetic trees derived from phylogenetic analyses of nuclear ribosomal and plastid DNA sequence data. Key Results: A total of 71 % of studied species have a bee pollination syndrome, 22 % a bimodal syndrome (Lepidoptera and bees), 3 % a bird pollination syndrome and 5 % a syndrome of autogamy, while 19 % of species have an asymmetrical corolla. Although floral symmetry and pollination syndromes are both evolutionarily labile, the latter shifts more frequently. Shifts in floral symmetry occurred mainly in the direction towards asymmetry, but there was considerable uncertainty in the pattern of shift direction for pollination syndrome. Shifts towards asymmetrical flowers were associated with a bee pollination syndrome. Conclusion: Floral evolution in Impatiens has occurred through both pollination syndrome shifts and divergent use of the same pollinator. Although the former appears more frequent, the latter is likely to be underestimated. Shifts in floral symmetry and pollination syndromes depend on each other but also partly on the region in which these shifts take place, suggesting that the occurrence of pollinator-driven evolution may be determined by the availability of pollinator species at large geographical scales.